Siddhartha - Hesse, Hermann (b, 2012)
Blends elements of psychoanalysis and Asian religions to probe an Indian aristocrat's efforts to renounce sensual and material pleasures and discover ultimate spiritual truths.
Keywords: Gautama Buddha -- Fiction; Buddhism -- Fiction; German fiction -- 20th century